A study on the effect of tyre rubber waste powder as partial sand replacement in cement mortar properties - Yuvaraj, Yathagan (2019)
Cement mortar is one of the most important materials widely used in construction industry. The production of cement mortar has a huge negative impact on nature and ecosystem. Many of nature based problems arises especially sand mining as sand is one of the main ingredient for cement mortar. Scrap tyres are also one of waste that drastically increasing day by day as the automobile industry progressing well. Improper disposal of waste tyre leads to pollutions and health issues. Hence, this research is carried out to help the industry to reduce the amount of waste at dump fill and also to reduce the dependency on sand solely in order to reduce sand mining which affects the nature and ecosystem. This research is basically to determine the effect of rubber waste powder content as partial sand replacement in cement mortar in terms of strength, workability and effect on temperature on rate of curing. The percentage of tyre rubber waste powder used to be tested were 0% (controlled), 5%, 10% and 15% .Total of five tests were conducted; compressive strength test, flexural test, flow table test, UPV test and temperature test. Prisms with size of (40 x 40 x 160) mm are used for flexural test and cube with the size of (50 x 50 x 50) mm used for the rest of the experiments. The compressive strength shows declination as the percentage of tyre rubber waste powder as sand replacement increases. The flexural test shows that 10% tyre rubber waste in cement mortar content has higher early strength on 3rd day but 5% has the highest flexural strength on 28th day has the highest compared to 10% and 15%. Flow table test indicates that the workability of the cement mortar increases as the percentage of tyre rubber waste increases in the cement mortar mix. UPV test shows that lesser the tyre rubber waste in cement mortar mix the lesser void and cracks exists. Temperature test shows that addition of tyre rubber waste powder increases the temperature of the fresh cement mortar. The optimum percentage of tyre rubber waste powder as sand replacement for the cement mortar in this research is 5%.